The Importance of Prenatal Whole-Exome Sequencing Testing in the Romanian Population - Ileana-Delia Săbău; Laurentiu-Camil Bohîltea; Viorica Elena Rădoi; Anca Mirela Bardan; Ovidiu Virgil Maioru; Mihaela Țurcan; Viorel Aurel Suciu-Lazar; Iuliana Ceausu (Journal of Mind and Medical Sciences, 2025)
One major cause of prenatal mortality and morbidity is congenital abnormalities. Knowing the prevalence and etiology of congenital malformations is essential for analyzing trends and improving neonatal care. Objective: the team aimed to evaluate the utility of whole-exome sequencing (WES) in Romanian prenatal care, highlighting its diagnostic efficacy in comparison to molecular karyotyping, particularly in cases with negative genetic results prior to WES, unfavorable pregnancy outcomes, and consanguinity. Methods: Initially, we identified pregnancies with abnormal ultrasounds unrelated to known syndromes. Subsequently, we performed SNP (single nucleotide polymorphism)-array testing, yielding negative results. We then applied prenatal WES, utilizing Massive Parallel Sequencing on the NovaSeq 6000 platform (average coverage > 100× read length: 2 × 100 bp) with library preparation using the Twist Human Core Exome kit RefSeq & Mitochondrial panel (Twist Bioscience). The bioinformatic analysis involved direct comparison to the human reference sequence (hg38). Results: We achieved a 50% diagnostic rate. After receiving results, two couples chose pregnancy termination, five had uneventful births, and one pregnancy ended in stillbirth. Additionally, we identified three incidental findings that enhanced patient and at-risk member management. This article details ten prenatal cases tested with WES, highlighting its superior diagnostic performance compared to the SNP array. WES detected the genetic diagnostic in 50% of cases that the SNP array did not. We emphasize the advantages of WES in prenatal diagnostics while acknowledging the need for further investigations to comprehensively evaluate its diagnostic utility in the Romanian population.